Who My Ideas Come from. Issue 2 (3rd April 2022) - Robbins, Maggie M.
Abstract: The activities of both art making and literary writing afford lots of mental space for the uncontrolled intervention by "creativity, " that difficult-to-describe-let-alone-define quality of original work. In this piece I will discuss the experience of creativity as an ego-dystonic force. Meaning no disrespect to the Muse, I will present this occurrence as a dissociative phenomenon.